Post-Tuberculosis Radiological Sequelae in Patients Treated for Pulmonary Tuberculosis: An Observational Study - Adhikari, Aarati; Shrestha, Shradha; Acharya, Rajesh; Mishra, Manish (Journal of College of Medical Sciences-Nepal, 2025)
Background Tuberculosis (TB) is a preventable and usually curable disease. However, the residual radiological lesions may persist even after the successful treatment. This study aims to assess the spectrum of post-TB radiological sequelae on chest CT scans in patients who have completed pulmonary TB treatment in a tertiary care facility. Methods A cross-sectional analytical study was conducted among 117 adult patients (18 years or above) with clinical or microbiological diagnosis of pulmonary TB and who completed the treatment for more than 1 year. Patients with previous history of other lung diseases like chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD), treatment failure and multidrug resistant (MDR) tuberculosis were excluded. A non-probability purposive sampling technique was used for data collection. Data was entered and analyzed by using SPSS-16. Results Out of total 117 cases of TB, residual lesions were seen in 104 cases (88.89%). Of the residual lesions, 54.80% were parenchymal, 6.7% were pleural and 2.9% were mediastinal. Overlap lesions like pleuro-parenchymal and parenchymal-mediastinal were 31.7% and 3.8% respectively. Conclusions A higher percentage of TB cases that were treated had residual radiological lesions. Pulmonary fibrosis was more common followed by pleural thickening.